Criterion validity and sensitivity to change of the Early Rehabilitation Index (ERI): results from a German multi-center study. (December 2016) - Rollnik, Jens; Bertram, M.; Bucka, C.; Hartwich, M.; Jöbges, M.; Ketter, G.; Leineweber, B.; Mertl-Rötzer, M.; Nowak, D.; Platz, T.; Scheidtmann, K.; Thomas, R.; et al.
Abstract Background Evaluation of functional status is difficult in neurological and neurosurgical early rehabilitation patients. The Early Rehabilitation Index (ERI) was introduced in Germany over 20 years ago, but since then validation studies are lacking. The ERI (range −325 to 0 points) includes highly relevant items including the necessity of intermittent mechanical ventilation or tracheostomy. Methods The present paper analyzed data from a German multi-center study, enrolling 754 neurological early rehabilitation patients. Together with ERI, Barthel Index (BI), Glasgow Coma Scale (GCS), Glasgow Outcome Score Extended, Coma Remission Scale (CRS), Functional Ambulation Categories and length of stay were obtained. Results ERI showed significant improvements from admission to discharge (p < 0.001). In addition, there were significant correlations of the ERI upon admission and at discharge with BI, CRS and GCS. Conclusions Evaluation of our study data suggest that the ERI may be used as a valid assessment instrument for neurological and neurosurgical early rehabilitation patients.